Chronometrical Evidence Supports the Model Theory of Negation - Guillermo Eduardo Macbeth; María del Carmen Crivello; Mauro Bruno Fioramonti; Eugenia Razumiejczyk (SAGE Open, 2017)
We aimed to study how compound negation of conjunctions and disjunctions is understood and represented. In particular, we aimed to test time course predictions consistent with the Mental Models Theory of negation proposed in 2012 by Khemlani, Orenes, and Johnson-Laird. Consistent with this theory, we conjectured that the consideration of possibilities elicited by any given information regulates the processing of compound negation. We studied response type patterns to replicate previous findings as well as response time patterns to generate novel chronometrical evidence. We conducted a within-subjects experiment to test a set of five experimental hypotheses. We used a sentence-equivalence task. Participants were asked to find a logical equivalence for a given compound negation of a conjunction or a disjunction. Four possible response options were presented, but only one of them was correct according to sentential logic. We also tested predictions derived from theories that argue against the Mental Models Theory. The evidence resulted consistent with the model theory of negation and incompatible with alternative accounts. In particular, our results did not support the Psychology of Proof and the Dual-Process approach to negation.